Lao People's Democratic Republic : Joint Staff Advisory Note on the Second Poverty Reduction Strategy Paper and Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Joint Staff Advisory Note reviews the National Socio-Economic Development Plan (NSEDP) 2006-10 and the Annual Progress Report for Lao People's Democratic Republic (PDR). The government of PDR approved the Sixth NSEDP 2006-10 (PRSP) in June 2006. The NSEDP provides a comprehensive strategy for development, with a range of medium- and long-term policies aimed at sustained growth and poverty reduction. IMF staff agrees with the poverty diagnosis in the NSEDP, but recognizes that achieving the Millennium Development Goals will require major efforts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet